2018
DOI: 10.1080/15384101.2018.1526600
|View full text |Cite
|
Sign up to set email alerts
|

CIZ1-F, an alternatively spliced variant of the DNA replication protein CIZ1 with distinct expression and localisation, is overrepresented in early stage common solid tumours

Abstract: CIZ1 promotes cyclin-dependent DNA replication and resides in sub-nuclear foci that are part of the protein nuclear matrix (NM), and in RNA assemblies that are enriched at the inactive X chromosome (Xi) in female cells. It is subjected to alternative splicing, with specific variants implicated in adult and pediatric cancers. CIZ1-F is characterized by a frame shift that results from splicing exons 8–12 leading to inclusion of a short alternative reading frame (ARF), excluding the previously characterized C-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
(90 reference statements)
0
5
0
Order By: Relevance
“…Additionally, earlier studies showed that CIZ1 binds DNA 49 and is present broadly in nuclei but only detectable by immunofluorescence (IF) (with two antibodies) after chromatin removal via a matrix protocol 50 ; hence, it was concluded that the CIZ1 epitope is masked by interaction with DNA. 47 , 51 Thus, we suggest that rather than XIST RNA recruiting CIZ1, CIZ1 is already present, but the epitope detected by a monoclonal antibody to the zinc finger region (DNA-binding domain) is masked in pluripotent cells, except when interacting with XIST RNA.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…Additionally, earlier studies showed that CIZ1 binds DNA 49 and is present broadly in nuclei but only detectable by immunofluorescence (IF) (with two antibodies) after chromatin removal via a matrix protocol 50 ; hence, it was concluded that the CIZ1 epitope is masked by interaction with DNA. 47 , 51 Thus, we suggest that rather than XIST RNA recruiting CIZ1, CIZ1 is already present, but the epitope detected by a monoclonal antibody to the zinc finger region (DNA-binding domain) is masked in pluripotent cells, except when interacting with XIST RNA.…”
Section: Resultsmentioning
confidence: 80%
“…Both CIZ1 and SAF-A have DNA- and RNA-binding domains thought to localize XIST RNA for its histone-modifying functions ( Figure 7C ); however, we propose an alternative concept for the role of CIZ1 or SAF-A, not as simply tethers for RNA but also as targets of XIST RNA. The immediacy with which XIST RNA triggers staining for CIZ1, together with the known masking of CIZ1 epitopes by interaction with DNA, 51 strongly suggests that XIST triggers a conformational change in CIZ1. We suggest that XIST RNA directly impacts the arrangement of one or more scaffold proteins and thereby modifies and condenses cytological-scale territory architecture ( Figure 7C ).…”
Section: Discussionmentioning
confidence: 99%
“…Rather than XIST RNA recruiting CIZ1 to the chromosome, these results suggest that CIZ1 is already there but the epitope detected by a monoclonal antibody is masked in pluripotent cells, except when interacting with XIST RNA. Indeed, earlier studies focused on CIZ1’s role in DNA replication (Coverley et al, 2005) showed that CIZ1 is present broadly in nuclei but only detectable by IF (with two antibodies) after chromatin removal in a matrix protocol; hence it was concluded that the CIZ1 epitope is masked by interaction with DNA (Ridings-Figueroa et al ., 2017; Swarts et al, 2018). Interestingly, CIZ1 is known to also bind DNA (Warder and Keherly, 2003) and the monoclonal antibody we used targets the zinc finger region.…”
Section: Resultsmentioning
confidence: 99%
“…Whether XIST RNA binding modifies CIZ1 conformation (to reveal the epitope) or recruits CIZ1, it is likely that XIST RNA is not just anchored by CIZ1 but impacts its interactions with other components. Given that CIZ1 binds DNA and becomes detected by IF after chromatin removal (Swarts et al ., 2018), an attractive hypothesis is that XIST RNA binding changes CIZ1-DNA interaction. A recent study from our lab shows that long euchromatin-associated CoT-1 hnRNAs (lncRNAs and pre-mRNAs) platform an insoluble RNP scaffold which counters chromosome condensation (Creamer et al ., 2021) hence this recent study and other evidence indicates XIST RNA may displace or silence RNAs that promote open euchromatin (Hall et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Cip1-interacting zinc finger protein 1 (CIZ1) is a nuclear protein implicated in DNA replication [ 6 ], cell cycle [ 7 , 8 ], apoptosis [ 9 , 10 ], transcriptional regulation [ 11 13 ], and maintenance of repressive chromatin at the inactive X chromosome (Xi) [ 14 , 15 ]. It has been linked with human pathologies including paediatric [ 16 , 17 ] and common adult-onset cancers [ 10 , 11 , 13 , 18 20 ] and with late onset neurological conditions [ 21 ] and Alzheimer’s disease [ 22 ], often as aberrant alternatively spliced variants [ 23 ]. A convincing mechanistic basis for the links with this diverse set of conditions is lacking, and there is no consensus on the underpinning defect or affected pathway.…”
Section: Introductionmentioning
confidence: 99%